How does green budget revenue policy promote economic sustainable development? Empirical evidence from 107 global economies - Li, Yushan; Meydan, Asli Gul; Wei, Chuanshuai; Zhao, Guoqin (Frontiers in Environmental Science, 2025)
Most existing studies have overlooked the role of green budgeting systems in channeling government and market resources toward environmentally sustainable sectors, thereby fostering sustainable economic development. In this study, we employ panel data from 107 global economies to examine the impact of green budget revenues (GBRs) on sustainable economic development and the mechanisms through which this relationship operates. The results indicate that GBRs significantly promote sustainable economic development across countries. In the short term, green budgeting exerts supervisory and demonstrative effects on firms’ production behavior. In the medium and long term, it enhances total factor productivity (TFP) by stimulating innovation compensation and by reshaping the allocation of traditional and green production factors, thus driving structural transformation in firms’ development models. Moreover, the positive impact of GBRs is stronger in non-OECD countries and in economies with lower fiscal pressure or varying levels of governance capacity. In this study, we reveal the medium- and long-term transmission mechanisms and cross-country heterogeneity of green budget policies, providing important theoretical and practical implications for governments seeking to design context-specific and targeted policy measures that jointly advance global sustainable development goals.